2022
DOI: 10.3390/metabo12070621
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome Features of COPD: A Scoping Review

Abstract: Chronic obstructive pulmonary disease (COPD) is a complex heterogeneous disease state with multiple phenotypic presentations that include chronic bronchitis and emphysema. Although COPD is a lung disease, it has systemic manifestations that are associated with a dysregulated metabolome in extrapulmonary compartments (e.g., blood and urine). In this scoping review of the COPD metabolomics literature, we identified 37 publications with a primary metabolomics investigation of COPD phenotypes in human subjects thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Furthermore, the vast majority of models described for the disease or its different circumstances have shown limited reproducibility in the validation steps. We agree with most authors of other recent reviews that there are still important deficits regarding the specific importance of factors such as age, sex, the temporal phases of the disease, its severity, exacerbations and progression trajectories to define more personalised metabolic profiles potentially susceptible of different future therapeutic approaches [ 48 , 150 152 ]. Moreover, the complementary use of relatively blind approaches such as those provided by wide metabolic screenings plus further cluster analyses will help to find still unknown endotypes and new pathophysiological mechanisms potentially involved in COPD.…”
Section: Limitations Of Previous Studies and Present Questionssupporting
confidence: 88%
“…Furthermore, the vast majority of models described for the disease or its different circumstances have shown limited reproducibility in the validation steps. We agree with most authors of other recent reviews that there are still important deficits regarding the specific importance of factors such as age, sex, the temporal phases of the disease, its severity, exacerbations and progression trajectories to define more personalised metabolic profiles potentially susceptible of different future therapeutic approaches [ 48 , 150 152 ]. Moreover, the complementary use of relatively blind approaches such as those provided by wide metabolic screenings plus further cluster analyses will help to find still unknown endotypes and new pathophysiological mechanisms potentially involved in COPD.…”
Section: Limitations Of Previous Studies and Present Questionssupporting
confidence: 88%
“…The aggregates (blue curve) meets the NMX-C-077- Table 2 Signals from sucrose identified from the EAP using 1 H, 13 C-NMR, and 1 H- 13 H and 13 C-NMR assignment based on Human metabolome database 2023. 44 Table 3 Signals from epicatechin identified from the EAP using 1 H, 13 C-NMR, and 1 H- 13 H and 13 C-NMR assignment based on Natsume et al 45 © 2024 The Author(s). Published by the Royal Society of Chemistry 1997-ONNCCE 30 (black curve) standard limits for ne aggregates (neness modulus = 2.8), thus conrming that it can be considered optimal for construction.…”
Section: Characterization Of the Aggregatesmentioning
confidence: 99%
“…Both sialic acid and hypoxanthine were found to be more elevated in patients experiencing common pulmonary exacerbations. Therefore, they could potentially serve as biomarkers for predicting future exacerbations and identifying patients at a higher risk for such events [ 40 ].…”
Section: Biological Matrices For Metabolomic Studies In Copdmentioning
confidence: 99%
“…It has been reported that serum and plasma metabolites of inflammation and oxidative stress could help recognize the development and exacerbation of COPD [ 40 ]. Moreover, plasma and sputum sphingolipid levels were higher in emphysema and COPD exacerbations [ 55 ].…”
Section: Application Of Metabolomics In the Study Of Copd: Biomarkers...mentioning
confidence: 99%